UNDERSTANDING THE DISCOURSE OF RADICALISM (CRITICAL APPROACH) - Karmuji Abu Safar; Asep Masykur; Sunardi Bashri Iman; Zenal Arifin; Mastori Mastori (Profetika: Jurnal Studi Islam, 2024)
Radicalism is an issue that is often identified with the religious thoughts and practices of Muslims. Even though the narrative of radicalism is claimed to be a neutral term various scientific studies, media reports, and public opinion tend to direct these radical accusations against certain Islamic understandings and certain Muslims. Using a qualitative descriptive method, this research tries to explain radicalism with various critical perspectives. Therefore, the term radicalism is studied in depth both from the terminology meaning and the development of meaning that occurs in the term radicalism. The results of the study show: that first, radicalism is not an Islamic terminology but a term that emerged from the West to characterize certain groups of Western society. Second, academically, the term radicalism is a neutral term and even tends to be positive. This term becomes negative because it is ridden by political interests. Third, every religion has a radical character, which has principal and basic teachings.